Alternative use of chromatic and achromatic cues in a hawkmoth - Kelber, Almut (The Royal Society, 2005)
The diurnal hummingbird hawkmoth Macroglossum stellatarum can learn the achromatic (intensity-related) and the chromatic (wavelength-related) aspect of a spectral colour. Free-flying moths learn to discriminate two colours differing in the chromatic aspect of colour fast and with high precision. In contrast, they learn the discrimination of two stimuli differing in the achromatic aspect more slowly and less reliably. When trained to use the chromatic aspect, they disregard the achromatic aspect, and when trained to use the achromatic aspect, they disregard the chromatic aspect, at least to some degree. In a conflicting situation, hummingbird hawkmoths clearly rely on the chromatic aspect of colour. Generally, the moths pay attention to the most reliable cue that allows them to discriminate colours in the learning situation. This is usually the chromatic aspect of the colour but they can learn to attend to the achromatic aspect instead. There is no evidence for relative colour learning, i.e. moths do not learn to choose the longer or shorter of two wavelengths, but it is possible that they learn to choose the darker or brighter shade of a colour, and thereby its relative intensities.